PELUANG EKONOMI SYARIAH PADA ERA MASYARAKAT EKONOMI ASEAN - Najamuddin Khairur Rijal; Zulfiyah Yasin (UNIDA Gontor, 2017)
This paper discusses the opportunities of Islamic economy in the era of AEC,especially in Indonesia. As understood, AEC is ASEAN’s cooperation and integration development that aims to easily the liberalization process in Southeast Asia by eliminating trade barriers in goods and services, capital, investment and labor. In this regard, it is important to study how the opportunities of Islamic economy as an Islamic-based economic perspective and practice, which is diametrically different from the perspective and practice of liberal economy in the AEC. This paper arguments are, first, Indonesia provides opportunities for Islamic economy development. Because, the number of Indonesian Muslim population is majority and Indonesia is ranked sixth in2016 as a country that has the potential and conducive in the Islamic financeindustries development. Second, Indonesian Islamic banking can become a state power in line with its existence and development from year to year, both in quantities and amount of assets. Third, the opening of the Jakarta Islamic Index proves that Islamic economy has its own market share and has a very strategic prospect amid the competition of AEC.